2019
DOI: 10.1002/joa3.12294
|View full text |Cite
|
Sign up to set email alerts
|

Longer diagnosis‐to‐ablation time is associated with recurrence of atrial fibrillation after catheter ablation—Systematic review and meta‐analysis

Abstract: Background Diagnosis‐to‐ablation time (DTAT) has been postulated to be one of the predictors of atrial fibrillation (AF) recurrence, and it is a “modifiable” risk factor unlike that of many electrocardiographic or echocardiographic parameters. This development may change our consideration for ablation. In this systematic review and meta‐analysis, we aim to analyze the latest evidence on the importance of DTAT and whether they predict the AF recurrence after catheter ablation. Methods We performed a comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
1
9
0
1
Order By: Relevance
“…In this meta-analysis, we also evaluate whether diagnosisto-ablation time and heart failure, which are shown to affect AF recurrence, 47,48 influence the association between obesity and AF recurrence. The regression analysis showed that the aforementioned covariates did not significantly influence the association.…”
Section: Af Ablationmentioning
confidence: 99%
“…In this meta-analysis, we also evaluate whether diagnosisto-ablation time and heart failure, which are shown to affect AF recurrence, 47,48 influence the association between obesity and AF recurrence. The regression analysis showed that the aforementioned covariates did not significantly influence the association.…”
Section: Af Ablationmentioning
confidence: 99%
“…CFRF vs. cryoenergy), the difference in the clinical outcomes might be at least partially explained by the relatively short mean time from the first AF episode to PVI in the C2C study (15 months), when compared to our study population (51.5 ± 46.9 months). Recent evidence, 21–24 in fact, suggests that an increased time between the first diagnosis of AF and catheter ablation might adversely affect long‐term outcomes, increasing the risk of AF recurrence in the follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…Комбинированная оценка этиологических факторов и признаков, ассоциированных с ПКМ, может быть полезной информацией при выборе стартовой медикаментозной терапии, в то время как анализ степени фиброза, электрических свойств и функции ЛП могут иметь решающее значение при выборе инвазивных методов лечения. Так, электромеханические и структурные (фиброз) маркеры ПКМ продемонстрировали прогностическую значимость в оценке риска рецидивирования ФП после катетерной РЧА в ряде исследований [49][50][51]. Результаты этих иссле дований дополняют наши знания, показывают связь между ремоделированием предсердий и эффектив ностью РЧА.…”
Section: Discussionunclassified